Economic impact of pharmaceutical interventions made in a renal transplant unit of a university hospital - Deise Talyse MELO; Alene Barros OLIVEIRA; José Alcântara NETO; Cinthya Cavalcante ANDRADE; Alisson Menezes LIMA; Glaydiane Alves SOUSA; Lizandra Máximo OLIVEIRA; Thaynara Carvalho FREITAS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To analyze the economic impact (EI) of pharmaceutical interventions (PI) made in a kidney transplant unit of a university hospital, through PI identification, EI classification and quantification of these. Methods: The observational cross-sectional study, descriptive study with retrospective data collection evaluated the PI records performed in a renal transplant infirmary in the period between June 2017 and June 2020, performed through the records on service-specific forms and database of the institution's clinical pharmacy unit. The economic impact was classified as: increase in effectiveness (IE); low cost (LC); avoided cost (AC), calculated through methodologies already developed and adapted to the reality of the study, were verified the costs of purchases of medicines in the hospital's own system and the values found adjusted to inflation of the years. The EI was classified according to the PI that had the potential to improve the medication use process and/or clinical effectiveness. In this classification, a real value of zero was assigned for the economic impact, even if the recommendation increased the value of the treatment. The RC was classified when the PI that included the cost was the one that felt the value of the treatment when compared with the previously administered therapeutic strategy without causing harm; and to classify as an AC the PI that was suggested to prevent or manage an Adverse Drug Event (ADE).Results: 873 PI were performed, of which 60.78% (n = 496) were of the type IE, 28.92% (n = 236) reduced cost and 10.30% (n = 84) avoided cost. The values found, were R$ 68,817.64 real (US$ 13.138,15 dollars) costs reduced, R$ 133,433.40 real (US$ 25.474,11 dollars) avoided, resulting in the final value of EI R$ 202,251.04 real (US$ 38.612,26 dollars). Conclusion: It is concluded that the implementation of Pharmaceutical interventions (IP) with Economic Impact (IE) and the use of pharmacoeconomic assessments function as an important strategy for optimizing resources and costs, combined with the search for ideal pharmacotherapy and improving clinical and economic.